2021
DOI: 10.1200/jco.2021.39.15_suppl.8518
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging phased variants for personalized minimal residual disease detection in localized non-small cell lung cancer.

Abstract: 8518 Background: Detection of circulating tumor DNA (ctDNA) has prognostic value in lung cancer and could facilitate minimal residual disease (MRD) driven approaches. However, the sensitivity of ctDNA detection is suboptimal due to the background error rates of existing assays. We developed a novel method leveraging multiple mutations on a single cell-free DNA molecule (“phased variants” or PVs) resulting in an ultra-low error profile. Here we develop and apply this approach to improve MRD in localized NSCLC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In 2021, Kurtz et al developed a new technology, termed Phased Variant Enrichment and Detection Sequencing (PhasED-Seq) (Foresight Diagnostics Inc., Aurora, CO, USA), to improve the sensitivity of ctDNA MRD detection [ 120 , 123 ]. Assays that utilize molecular barcoding, such as CAPP-Seq, rely on duplex sequencing to improve the limit of detection, but duplex strand recovery is often suboptimal in the MRD setting [ 41 , 124 ].…”
Section: Minimal Residual Disease (Mrd) Detectionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2021, Kurtz et al developed a new technology, termed Phased Variant Enrichment and Detection Sequencing (PhasED-Seq) (Foresight Diagnostics Inc., Aurora, CO, USA), to improve the sensitivity of ctDNA MRD detection [ 120 , 123 ]. Assays that utilize molecular barcoding, such as CAPP-Seq, rely on duplex sequencing to improve the limit of detection, but duplex strand recovery is often suboptimal in the MRD setting [ 41 , 124 ].…”
Section: Minimal Residual Disease (Mrd) Detectionmentioning
confidence: 99%
“…Using this novel strategy, the authors showed that PhasED-Seq outperforms duplex sequencing with CAPP-Seq, yielding a limit of detection below one part per million [ 123 ]. PhasED-Seq was then applied to 14 plasma samples, collected from five patients with localized NSCLC, for MRD detection [ 120 ]. PhasED-Seq detected ctDNA MRD in 10 of the 14 samples, while a SNV-based ctDNA method only detected MRD in 5 of the 14 samples.…”
Section: Minimal Residual Disease (Mrd) Detectionmentioning
confidence: 99%
See 3 more Smart Citations